Rede social, memória e identidade : a elite imigrante portuguesa em Pelotas-RS, 1910-1992 - análise biográfica de Aníbal de Oliveira Vidal e Maximiano Pombo Cirne - Jaques, Biane Peverada (2021)
The present thesis addresses the theme of immigration of Portuguese origin, specifically from the region of Aveiro to Pelotas / RS, Brazil, between the years 1910 and 1992. The chronological outline of the research is guided, above all, by the year of birth and death of two specific immigrants, Aníbal de Oliveira Vidal and Maximiano Pombo Cirne. On the other hand, the spatial outline of the thesis is defined by the locations of origin and destination, established from a specific migratory chain, which Aníbal and Maximiano were part of. The theoretical-methodological approach of the text corresponds to the biographical analytical assumptions, widely used in studies about immigration, however, little used with the Portuguese origin. The main objective of the thesis is to identify and analyze the establishment and the functionality of the social network - with elite characteristics - to which the biographies were part. Therefore, it is necessary to identify some established social connections and, from them, understand how the group related to each other and to society. Thus, as a result of the relationships established internally and externally to the group, it is possible to analyze the affirmation of their ethnic identity. The main source used was the documentation found in the private personal archives of Aníbal and Maximiano. Information from oral history interviews, Brazilian and Portuguese archives was also analyzed.